2003
DOI: 10.1897/1551-5028(2003)022<0706:adolas>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Degradation of Linear Alkylbenzene Sulfonate

Abstract: Linear alkylbenzene sulfonate (LAS) found in wastewater is removed in the wastewater treatment facilities by sorption and aerobic biodegradation. The anaerobic digestion of sewage sludge has not been shown to contribute to the removal. The concentration of LAS based on dry matter typically increases during anaerobic stabilization due to transformation of easily degradable organic matter. Hence, LAS is regarded as resistant to biodegradation under anaerobic conditions. We present data from a lab-scale semi-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
(20 reference statements)
2
11
0
4
Order By: Relevance
“…Our findings of 40-80% LAS removal in the UASB reactors are consistent with reported values in the range of 37-85% (Mogensen, 2001;Mogensen and Ahring, 2002;Mogensen et al, 2003;Sanz et al, 2003). Mogensen (2001) has furthermore reported that LAS are more efficiently removed in thermophilic compared with mesophilic UASB reactors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings of 40-80% LAS removal in the UASB reactors are consistent with reported values in the range of 37-85% (Mogensen, 2001;Mogensen and Ahring, 2002;Mogensen et al, 2003;Sanz et al, 2003). Mogensen (2001) has furthermore reported that LAS are more efficiently removed in thermophilic compared with mesophilic UASB reactors.…”
Section: Discussionsupporting
confidence: 93%
“…Although anaerobic LAS degradation has been reported, metabolic pathways are not yet understood. The limited information so far indicates that (1) LAS can be used as a source of sulfur by anaerobic bacteria under sulfur limited conditions (Denger and Cook, 1999), and (2) benzenesulfonic acid and benzaldehyde may be produced as metabolites during anaerobic LAS degradation Mogensen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Many works have been done to confirm the complete biodegradability of LAS (Almendariz et al 2001;Sanz et al 2003;Mogensen et al 2003;Lobner et al 2005). Anaerobic degradation requires a consortium of bacteria that act on different parts of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic degradation requires a consortium of bacteria that act on different parts of the molecule. For example, the biodegradation of LAS requires alteration of an alkyl chain, a benzene ring and a sulfonate linkage (Mogensen et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, evidence of LAS biodegradation without oxygen has been found when anaerobic treatment is preceded by aerobic exposure (Larson et al 1993). Mogensen et al (2003), have reported the anaerobic biodegradation of LAS by granular sludge using UASB reactors. In addition, desulfonation of LAS has been reported to occur by anaerobic bacteria in the laboratory (Denge & Cook 1999).…”
Section: Introductionmentioning
confidence: 99%